Narrating Personal and Collective History in Heritage Tourism:: Conflicting Representations of the São Domingos Mine and Community - P. Silva, Maria (Material Culture Review)

(untitled) (National Museums of Canada, 2010)
Abstract This paper explores the complexities and contradictions, as well as the progressive potential of industrial heritage tourism sites. It considers how industrial heritage sites may enable, if not foster, the communication of personal and collective stories and experiences of past crafts and ways of life, along with the oppression, exploitation and abandonment that often comes with industry. The focus of the essay is the ongoing recast into an industrial heritage tourism destination of a former mining village and complex in Portugal. Built and run by an English mining company during the mid 19th century, the mine operated until the 1960s. Three representations of the history of the S. Domingos mine and community are analyzed and confronted, namely two exhibitions prepared for the 150th anniversary of the founding of the mine, a painting, photography and multimedia exhibition, and a book written and self published by a former miner.